Tradeoff between energy and user experience for multimedia cloud computing. (October 2015) - Liu, Yunchang; Li, Chunlin; Yang, Zhiyong
Graphical abstract: Highlights: We investigate the trade-off of QoE and energy in multimedia cloud. A QoE quantifying model is proposed based on objective factor. We develop a theoretic model by applying Lyapunov optimization method. An approximate online algorithm (EUE-RP) is proposed with the explicitly provable performance upper bound. The proposed method flexibly manages the trade-off between QoE and energy for cloud-based multimedia services. Abstract: Cloud computing provides an effective approach to deliver multimedia services to end users with the desired user quality of experience (QoE). However, cloud-based multimedia applications require many of servers and consume huge energy. To reduce energy consumption, a multimedia service provider (MSP) should balance the energy and QoE. In this paper, a theoretic model is developed to explore the trade-off between energy consumption and QoE for multimedia cloud. Based on objective factor, a QoE quantifying model is proposed. Employing Lyapunov Optimization techniques, an optimal control framework is designed and analyzed to make energy and QoE decisions in MSPs. An approximate online algorithm (EUE-RP) is proposed with the explicitly provable performance upper bound. Extensive experiments have been conducted to verify the effectiveness of EUE-RP algorithm in the practical settings. The algorithm can guarantee desired QoE and reduce energy consumption, even without any information about the future fluctuation of user demands.